Early electrophysiological markers of atypical language processing in prematurely born infants. (December 2015) - Paquette, Natacha; Vannasing, Phetsamone; Tremblay, Julie; Lefebvre, Francine; Roy, Marie-Sylvie; McKerral, Michelle; Lepore, Franco; Lassonde, Maryse; Gallagher, Anne
Abstract: Because nervous system development may be affected by prematurity, many prematurely born children present language or cognitive disorders at school age. The goal of this study is to investigate whether these impairments can be identified early in life using electrophysiological auditory event-related potentials (AERPs) and mismatch negativity (MMN). Brain responses to speech and non-speech stimuli were assessed in prematurely born children to identify early electrophysiological markers of language and cognitive impairments. Participants were 74 children (41 full-term, 33 preterm) aged 3, 12, and 36 months. Pre-attentional auditory responses (MMN and AERPs) were assessed using an oddball paradigm, with speech and non-speech stimuli presented in counterbalanced order between participants. Language and cognitive development were assessed using the Bayley Scale of Infant Development, Third Edition (BSID-III). Results show that preterms as young as 3 months old had delayed MMN response to speech stimuli compared to full-terms. A significant negative correlation was also found between MMN latency to speech sounds and the BSID-III expressive language subscale. However, no significant differences between full-terms and preterms were found for the MMN to non-speech stimuli, suggesting preserved pre-attentional auditory discrimination abilities in these children. Identification of early electrophysiological markers for delayed language development could facilitate timely interventions.